PEMBUATAN ARANG AKTIF DARI TEMPURUNG KELAPA, SERBUK KAYU, TEMPURUNG DAN TANDAN KELAPA SAWIT - Gustan Pari; Sasa Abdurrohim (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
The aim of this experiment was to learn the properties/characteristics of activated charcoal manufacturedfrom various lignocellulosic materials, i.e. coconut shell, oilpalm bunches, wood sawdust (sawn from mixed forest wood species), and empty oilpalm bunches.At first, each of the four lignocellulosic materials was carbonized into charcoal under the particular conditions, as follows : the materials converted to small particles with 0.3 0.5 cm size, an implementing carbonization temperature at 500oC. The charcoal was activated using the condition: activating temperature at 900oC for 30 minutes, and exercising air flow rate at 800 I,100oC. The variables implemented in this experiment were kinds of raw materials (i.e. 4 kinds as previously mentioned), and soaking in 1 percent NaOH (alkali) for 24 hours which was further compared with the one without soaking.Charcoal properties showed that coconut shell obtained the highest in fixed carbon content, the lowest in volatile matter and ash. Results in activated charcoal analyses showed that coconut shell obtained the highest in yield (50.5%) while the empty fruit bunch was the lowest (29.3%). The coconut shell also obtained the highest in fixed carbon (85.9%) while the lowest was saw dust (69.1%).Soaking treatment showed better quality on most of activated charcoal properties. Coconut shell gave the highest in benzene adsorption (20.17%) and iod adsorption (881.8 mg/g). In general, other raw materials showed low adsorption to benzene, while most of them has been met the AWWA B.600 78 standard or iod adsorption. The CPO refining showed that saw dust activated charcoal gave the best in refining (54.8% transmission) followed by empty fruit bunch, coconut shell and oil palm shell.